Determine The Lifespan for Components in Automatic Platform Gate (APG) And Platform Screen Door (PSD) for Klang Valley MASS Rapid Transit (KVMRT) Putrajaya Line Project - Ramli@Rusdi, Muhammad Ridhauddin; Bin Hasnan, Khalid; Bin Zuklivly, Zariq Zdorieve (Progress in Engineering Application and Technology, 2022)
KVMRT Putrajaya Line is a project developed to meet the needs of consumers for public transport in Malaysia. The project is divided into two phases, namely Phase 1 and Phase 2. Phase 1 is expected to operate at the Mid-June of 2022 while Phase 2 is expected to operate in 2023. This study only focuses on Phase 2 as all information and data are taken from Phase 2. This project is one of the mega projects in Malaysia and is equipped with various modern technologies and structures. APG and PSD are one of the modern structures found in this project. APG and PSD operations require a lot of cycle motion due to the high rate of train operation throughout the day. Since the APG and PSD require a lot of cycle motion, then the components found on both structures must have a long lifespan to accommodate the operation of the APG and PSD. The important components that run APG and PSD operations such as Electromagnetic Locking Device (ELD), Gate Control Unit (GCU), Door Control Unit (DCU) and limit switches have a certain period before being converted to new ones. There are two levels of APG and PSD testing, namely the Partial Acceptance Test (PAT) and System Acceptance Test (SAT). The PAT requires both structures to reach 240 cycles while the SAT requires 1000 cycles to pass the test. Problems occur when both structures fail to pass the PAT and SAT causing the process to complete the project to stagnate. This research aims to determine the lifespan components in APG and PSD operation based on PAT and SAT conducted over a period of seven days. The results of the recorded data will be analyzed and maintenance scheduling can be determined for long-term plans.